Micro Teaching Skills for Health Professionals - Chaudhary, Nagendra; Mahato, Shyam Kumar; Chaudhary, Shatdal; Bhatia, Bal Dev (Journal of Universal College of Medical Sciences, 2015)
Microteaching, a teacher training technique, provides teachers an opportunity to develop their teaching skills by self- practice and self-criticism. It is not at all a teaching method rather than it is a device for skill practice. All health professionals should have proper teaching skills for transfer of their knowledge which can be acquired by microteaching sessions. This article focusses on the need for microteaching, the process and its advantages. INTRODUCTION: The art of teaching not only means a simple transfer of knowledge from one to other, instead, it is a complex process which facilitates and influences the process of learning. Medical professionals always feel that their education does not prepare them for teaching. Quality of a teacher is evaluated on how much the students can understand from his/her teaching. The classrooms cannot be used as a learning platform for acquiring primary teaching skills. Training of medical teachers in specific teaching skills is a major challenge in medical education programs. However, society's increasingly high expectations on health professionals demand that they be taught and trained effectively. The traditional medical teaching emphasizes on the transmission of factual knowledge and hence, the teachers are the main source of information. But, the conventional methods of medical teacher training are not adequate. So, the teaching objectives have now shifted to the student centered, measurable, achievable, relevant, and timely concept. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 60-64